Sabellianism and the Trinity Doctrine: A Historical and Apologetic Review - Hendij Ofian Tololiu (Asosiasi Dosen Muda Indonesia, 2026)
Sabellianism, also known as Modalistic Monarchianism, emerged during the third century as an attempt to preserve the absolute unity of God. However, this teaching was later rejected by the early Christian Church because it interpreted the Father, the Son, and the Holy Spirit merely as different modes or manifestations of one divine Person rather than three distinct and eternal Persons. This study aims to examine the historical background and principal teachings of Sabellianism and to compare them with the doctrine of the Trinity from historical, biblical, and apologetic perspectives. The study employed a qualitative library research method using a descriptive-analytical and comparative approach. Primary sources included biblical texts and the writings of the early Church Fathers, while secondary sources consisted of theological, historical, and apologetic literature. The analysis demonstrates that Sabellianism is inconsistent with the biblical testimony concerning the eternal relationship between the Father, the Son, and the Holy Spirit. The baptism of Jesus, the Great Commission, and other biblical passages consistently affirm the coexistence and distinction of the three divine Persons while maintaining the unity of the divine essence. Historically, the early Church rejected Sabellianism and affirmed the doctrine of the Trinity through the formulations of the Councils of Nicaea and Constantinople. This study concludes that the doctrine of the Trinity provides the most coherent theological framework for understanding the biblical revelation of God and serves as an essential foundation for Christian apologetics in explaining and defending the Christian faith.